2008
DOI: 10.1063/1.2827487
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and size effects in endohedrally confined hydrogen clusters

Abstract: Density functional theory is used to carry out a systematic study of zero-temperature structural and energy properties of endohedrally confined hydrogen clusters as a function of pressure and the cluster size. At low pressures, the most stable structural forms of (H(2))(n) possess rotational symmetry that changes from C(4) through C(5) to C(6) as the cluster grows in size from n=8 through n=12 to n=15. The equilibrium configurational energy of the clusters increases with an increase of the pressure. The rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 51 publications
2
27
0
1
Order By: Relevance
“…According to our previous investigations, this is the pressure range where metalization and atomization of the hydrogen cluster show up. 6 Other vibrations of H 26 also exhibit breathing character but their bc numbers are substantially lower with respect to these of doped clusters. In the low pressure region, the frequencies of the doped clusters are relatively close to the frequencies of H 26 ; however, the differences become slightly more pronounced in the high pressure region.…”
Section: Vibrations With Breathing Charactermentioning
confidence: 97%
See 1 more Smart Citation
“…According to our previous investigations, this is the pressure range where metalization and atomization of the hydrogen cluster show up. 6 Other vibrations of H 26 also exhibit breathing character but their bc numbers are substantially lower with respect to these of doped clusters. In the low pressure region, the frequencies of the doped clusters are relatively close to the frequencies of H 26 ; however, the differences become slightly more pronounced in the high pressure region.…”
Section: Vibrations With Breathing Charactermentioning
confidence: 97%
“…3 We use a general methodology developed for clusters under confinement along several papers. [4][5][6][7][8][9] By using this methodology, it was found that doped hydrogen clusters reach the metallic state at lower pressures than the pure hydrogen species. In an attempt to go along the same line, we compare here the vibrational spectra of pure hydrogen clusters with the corresponding spectra of doped hydrogen clusters.…”
Section: Introductionmentioning
confidence: 99%
“…"Confined Quantum Systems Using the Finite Element and Discrete Variable Representation Methods" [21] is a review of its Refs. [9,11,17,50,58,62,63,68,74,76,89,90,91,117,124] by the same Authors, in which they have developed and applied the methods in the title to a variety of quantum systems under different situations of confinement. Section 4 illustrates some of these specific applications showing numerical results matching favorably the most accurate in the literature.…”
Section: 25mentioning
confidence: 99%
“…Then, by following standard rules of analytical mechanics, the Lagrangian equations of motion are obtained. The model provides a formal framework for the previous studies of the hydrogen gas under the effects of pressure and temperature [4][5][6][7][8][9][10][11]. Contrary to other proposed models, the present model includes a representation of the medium surrounding the system of the confined particles by a direct inclusion of such properties as the structure and rigidity of the container, the viscosity of the fluid forming the surrounding medium, etc., described in terms of mechanical and statistical mechanics axioms.…”
Section: Introductionmentioning
confidence: 96%